Epidemiology, Biostatistics and Public Health, EBPH: a new vision for two old journals - Stefania Boccia; Carlo La Vecchia (Epidemiology, Biostatistics and Public Health)
The launch of this new journal, Epidemiology, Biostatistics and Public Health (EBPH), enables us to embrace new challenges, and renew our commitment to our readers, our authors and fellow editors, and ultimately to the public health community worldwide. EBPH is an open access journal streaming from two previous journals, one focused on public health (The Italian Journal of Public Health, http://ijphjournal.it/) [1-8], ...